THE EFFECT OF EMPLOYEE ENGAGEMENT, ORGANIZATIONAL CULTURE AND EMOTIONAL INTELLIGENCE TO WARDS ORGANIZATIONAL COMMITMENT ON EMPLOYEES OF PT. PERKEBUNAN NUSANTARA IX KEBUN SEMUGIH - Bagis, Fatmah; Irawati, Irawati; Rahmawati, Dwi Vina (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study is an analysis of the influence of employee involvement, organizational culture and emotional intelligence on organizational commitment at PT. Perkebunan Nusantara IX Kebun Semugih Pemalang. The population of this study were 143 employees with a sample of part of the employees of PT. Perkebunan Nusantara IX Kebun Semugih totaling 100 employees using purposive sampling technique and data obtained from respondents using a research instrument using a questionnaire. The research method used in this research is multiple regression analysis. The results showed that the variables of employee involvement, organizational culture and emotional intelligence simultaneously had a significant positive effect on organizational commitment. The results of the partial analysis test show that employee involvement has a significant positive effect on organizational commitment, organizational culture has a significant positive effect on organizational commitment and emotional intelligence has a significant negative effect on organizational commitment. Keywords: Employee Engagement, Organizational Culture, Emotional Intelligence and Organizational Commitment.